Control of suddenly expanded flow at low supersonic Mach numbers - Chaudhury, Zakir Ilahi; Shinde, V.B; Syed, Syed Ashfaq; Khan, Sher Afghan (IJERA, 2015)
In the present study the experiments were conducted to control the base pressure from a convergent-divergent nozzle at low supersonic Mach numbers to assess the effectiveness of active control mechanism in the form of micro jets at different expansion level. The parameters considered in the present study are the diameter ratio, length to diameter ratio (L/D), Nozzle Pressure Ratio (NPR), and the Mach number. The diameter ratio selected for the present study are 1.6, 1.8, 2.2, and 2.5. Experiments were conducted for nozzle pressure ratio (NPR) from 3 to 11. The L/D ratio of the enlarged duct was varied from 10 to 1, and results are presented for L/D 4, 3, 2, and 1. The Mach numbers of the present studies are 1.1, 1.2, 1.4, and 1.5. The results show that the Micro jets are very effective and are able to raise the base pressure value to a considerable level under the influence of favorable pressure gradient except at lower NPR 3. At NPRs 5 and 7 for some cases the trends differ due to the level of expansion, nature of waves present in the base region, relief available to the flow, L/D ratio of the enlarged duct and the Mach numbers. It is seen that most of the cases exhibit similar behavior for the L/Ds in the range 4 and 3, which means; that the back pressure has not adversely influenced the flow field in the base region as well as in the duct. The minimum duct length required for the flow to be attached is L/D = 2, even though in some cases flow is attached with duct wall. With this it can be stated that the micro jets can be an alternative for the for base pressure control. Keywords - Base pressure, Length-to-diameter ratio, Mach number, Nozzle pressure ratio, Sudden expansion